Design and Implementation of a Secure AI-Based Product Showcase and Customer Support System for Small and Medium-Sized Enterprises - OLASUNKANMI, Hammed A.; ADENIJI, Olumuyiwa I.; LAWAL, Mufutau K.; OJO, Babatola E.; OMOWOLE, Babayemi D.; AVAH, Somtochukwu E.; ADELEKE, Isiaka A.; POPOOLA, Kudirat N.; IBITOYE, Ademidun E. (FUDMA Journal of Engineering and Technology, 2026)
This paper presents the development and evaluation of a secure artificial intelligence-driven product showcase and customer support system designed specifically for Small and Medium-Sized Enterprises (SMEs). The proposed platform combines product presentation, an AI-powered customer support chatbot, a content-based recommendation engine and integrated security mechanisms within a unified web application to improve customer engagement, product accessibility and data protection. A hybrid dataset consisting of 2,050 product records obtained from TY Supermarket, Iree, Osun State, Nigeria and a publicly available Kaggle e-commerce dataset was used for model training and system evaluation. Textual data were transformed into numerical features using the Term Frequency–Inverse Document Frequency (TF-IDF) technique, while the Multinomial Naive Bayes algorithm was employed to classify customer intents. Product recommendations were generated using a Content-Based Filtering approach based on Cosine Similarity. To safeguard user and business information, the system incorporated Role-Based Access Control (RBAC), secure password hashing, authentication and session management. Performance evaluation showed that the chatbot achieved an accuracy of 95.50%, precision of 95.55%, recall of 95.50% and an F1-score of 95.51%, whereas the recommendation module attained an accuracy of 93.80%. User acceptance was further evaluated through a five-point Likert-scale questionnaire administered to 40 participants, producing an overall satisfaction score of 95.00%. The findings indicate that the developed system enhances customer interaction, facilitates efficient product discovery, improves operational efficiency and strengthens information security. Consequently, the proposed framework provides an affordable, intelligent and secure digital business solution capable of supporting the digital transformation of SMEs.
Keywords: Artificial Intelligence, Product Showcase, Customer Support, Chatbot, Multinomial Naive Bayes.